Podocyte-Derived BMP7 Is Critical for Nephron Development - Kazama, Itsuro (American Society of Nephrology, 2008)
Individuals with congenital renal hypoplasia display a defect in the growth of nephrons during development. Many genes that affect the initial induction of nephrons have been identified, but little is known about the regulation of postinductive stages of kidney development. In the absence of the growth factor bone morphogenic protein 7 (BMP7), kidney development arrests after induction of a small number of nephrons. The role of BMP7 after induction, however, has not been fully investigated. Here, we generated a podocyte-specific conditional knockout of BMP7 (Bmp7(flox/flox);Nphs2-Cre(+) [BMP7 CKO]) to study the role of podocyte-derived BMP7 in nephron maturation. By postnatal day 4, 65% of BMP7 CKO mice had hypoplastic kidneys, but glomeruli demonstrated normal patterns of laminin and collagen IV subunit expression. Developing proximal tubules, however, were reduced in number and demonstrated impaired cellular proliferation. We examined signaling pathways downstream of BMP7; the level of cortical phosphorylated Smad1, 5, and 8 was unchanged in BMP CKO kidneys, but phosphorylated p38 mitogen-activated protein kinase was significantly decreased. In addition, β-catenin was reduced in BMP7 CKO kidneys, and its localization to intracellular vesicles suggested that it had been targeted for degradation. In summary, these results define a BMP7-mediated regulatory axis between glomeruli and proximal tubules during kidney development.